The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.21203/rs.3.rs-1920871/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First-in-human diagnostic study of hepatic steatosis with computed ultrasound tomography in echo mode (CUTE)

Abstract: Non-alcoholic fatty liver disease is rapidly emerging as the leading global cause of chronic liver disease. Efficient disease management requires low-cost, noninvasive techniques for diagnosing hepatic steatosis accurately. Here we propose quantifying liver speed-of-sound (SoS) with computed US tomography in echo mode (CUTE), a newly developed US imaging modality adapted to clinical pulse-echo systems. CUTE reconstructs the spatial distribution of SoS by measuring local echo phase shifts when probing tissue at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Extending the methods from this paper for real-time layer-wise (as opposed to global) SoS estimation in vivo is another direction that our group is currently developing, following a similar trend as in [25]. Frameworks that have real-time capability for performing SoS estimation layer-wise, region-wise, or locally can be extremely useful for improved quantification of tissue health via the SoS biomarker [13].…”
Section: Limitations and Future Workmentioning
confidence: 94%
See 2 more Smart Citations
“…Extending the methods from this paper for real-time layer-wise (as opposed to global) SoS estimation in vivo is another direction that our group is currently developing, following a similar trend as in [25]. Frameworks that have real-time capability for performing SoS estimation layer-wise, region-wise, or locally can be extremely useful for improved quantification of tissue health via the SoS biomarker [13].…”
Section: Limitations and Future Workmentioning
confidence: 94%
“…After all, the SoS, being an intrinsic acoustic property of human tissues, can potentially serve as a biomarker for tissue composition. Indeed, studies have shown that tissue SoS can help to assess intramuscular fat content [4], [5], detect age-related or cast-related muscle decay [6], [7], differentiate between benign and malignant tumors [8]- [10], and quantify accumulation of fat in the liver [11]- [13]. It would be advantageous to clinically derive tissue SoS estimates and, preferably, render this biomarker in parallel to real-time Bmode imaging that is known for its bedside applicability [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CUTE has shown promising results in tissue-mimicking phantoms and in vivo [ 19 , 21 ]. In vivo echo shift data are, however, often marked by systematic elevated noise that can arise due to attenuation, aberration, and reverberations, among others, introducing artifacts in the SoS map.…”
Section: Introductionmentioning
confidence: 99%
“…This is the approach used in computed tomography in echo mode (CUTE), which tracks echo phase shifts caused by SoS heterogeneities when probing tissue at different angles [8]- [10]. CUTE has demonstrated unprecedented spatial and contrast resolution in tissue-mimicking phantoms [11] and is currently undergoing clinical evaluation [12]. This work presents an extension of CUTE to quantify the spatial distribution of US ATT in tissue.…”
Section: Introductionmentioning
confidence: 99%